Survival strategies of the salamander Desmognathus ochrophaeus: interaction of predator-avoidance and anti-predator mechanisms - Hileman, Kendra S.; Brodie, Edmund D. (Animal behaviour, 1994)
The anti-predator responses of the mountain dusky salamander, Desmognathus ochrophaeus, to the larger predatory salamanders, Dunn's spring salamander, Gyrinophilus porphyriticus, and black-bellied salamander, D. quadramaculatus were examined in two types of experiments. In both experiments the prey species, especially those corresponding to the largest size subject to predation by these predators, fled from G. porphyriticus but not D. quadramaculatus when seasonal predator avoidance was low. Fleeing from G. porphyriticus was low when seasonal predator avoidance was high. The high fleeing response to G. porphyriticus corresponded to low post-attack anti-predator efficacy against G. porphyriticus. The low fleeing response to D. quadramaculatus corresponded to high post-attack anti-predator efficacy against D. quadramaculatus.